2017
DOI: 10.1038/srep42011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation and inconsistency between estimates of onset of muscle activation from EMG and ultrasound

Abstract: Delayed onset of muscle activation can be a descriptor of impaired motor control. Activation onset can be estimated from electromyography (EMG)-registered muscle excitation and from ultrasound-registered muscle motion, which enables non-invasive measurements in deep muscles. However, in voluntary activation, EMG- and ultrasound-detected activation onsets may not correspond. To evaluate this, ten healthy men performed isometric elbow flexion at 20% to 70% of their maximal force. Utilising a multi-channel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 54 publications
2
50
3
1
Order By: Relevance
“…Electrical stimulation produces small electromechanical delays around 10 ms and will activate all motor units within the region at once, thus eliminating the hierarchical activation of low‐threshold to high threshold motor units . However, in voluntary contractions, sEMG onset is regionally variable and contraction dependent . Previous studies comparing sEMG and ultrasound often report smaller differences with narrower confidence intervals than our current study.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…Electrical stimulation produces small electromechanical delays around 10 ms and will activate all motor units within the region at once, thus eliminating the hierarchical activation of low‐threshold to high threshold motor units . However, in voluntary contractions, sEMG onset is regionally variable and contraction dependent . Previous studies comparing sEMG and ultrasound often report smaller differences with narrower confidence intervals than our current study.…”
Section: Discussioncontrasting
confidence: 49%
“…As a follow‐up to their previous study, Dieterich et al demonstrated regional differences in sEMG onset using a transparent multi‐channel surface electrode array, suggesting that movement registered by ultrasound may not necessarily equate to electrical activation of the muscle in the sampling region. The authors also noted that ultrasound registered initial motion in the deeper region of the muscle.…”
mentioning
confidence: 69%
See 3 more Smart Citations